Genotoxicity of Argovit nanosilver particles in human lymphocytes in in vitro culture - Arellano-Garcia E.; Bogdanchikova N.; Burmistrov V.; Pestryakov A. N. Aleksey Nikolaevich; Ruiz-Ruiz B.; Luna R.; Casillas-Figueroa F.; Giron N. (2013, 2013)
В фонде НТБ ТПУ отсутствует